Contribuição ao estudo sobre o projeto estrutural de painéis em concreto pré-moldado - Santos, Bruno Pereira dos (Universidade Federal de São Carlos, 2016)
The use of building technologies as prefabricated concrete wall panels has been increasing as a common practice in the Brazilian market. An aspect in the use of panels in buildings, barely explored in Brazil, is the possibility of considering it actively contributing in responsiveness to loads imposed, interacting with other elements such as pillars, slabs and beams. Since it is known that the literature about the theme is very limited, and facing a new specific standard coming soon, ABNT NBR 16475 (2016), this study has as objective to review the concepts of design and dimensioning of precast wall panels. With a review of the most recognized literatures and previous research already made, as well as analysis of the current standards, is shown the major advances related to the research theme, as well the standards parameters and criteria used nowadays. Finally, it is exemplified in a mathematical model design, adopting the parameters and criteria mentioned on the standards studied, and the information obtained in the previous academic studies, making possible to bring discussions and analysis using parallels and comparisons, providing information that are subside for important conclusions for technical, academic and industrial segment of precast concrete, promoting an advance in the discussion of a very significant and actual theme.
Contribution to the study about the structural design of precast concrete wall panels
Keywords: Painéis pré-moldados; Concreto pré-moldado; Análise estrutural; Dimensionamento; Cálculo de estruturas; Precast concrete wall panels; Structural analysis; Structural design; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS